Particleboard produced with sawmill waste of different wood species - Alves, Luciane Simal [UNESP]; Mello da Silva, Sergio Augusto [UNESP]; Azambuja, Maximiliano dos Santos; Varanda, Luciano Donizeti; Christoforo, Andre Luis; Rocco Lahr, Francisco Antonio; Sung, W. P.; Chen, R. (Trans Tech Publications Ltd, 2014)
This study aimed to investigate physical performance of particleboards produced with waste from sawmills, containing different wood species, and two adhesives: urea-formaldehyde (UF) based resin and castor-oil (PU) based bi-component polyurethane resin. Panels were produced with nominal density 0.8gcm(-3); pressing temperature 110 degrees C; pressing time 10 min; specific pressure 5 MPa. Water absorption (2 and 24h); thickness swelling (2 and 24h); density; and moisture content were investigated. Results confirmed that the produced panels presented compatible physical properties in comparison with other researches referred in literature, proving the feasibility of inputs employed. Panels produced PU showed better performance than those produced with UF.
Keywords: Physical properties; residues; timber